Antibacterial Effects Various Types Of Honey And Citrus Juice On Streptococcus Pyogenes: A Systematic Review - Mohamed, NS; S.G. Pathmanathan; Ismail, Z; Sani, A; Rashid, ZZ; Mohamed, NA; Khairun Nain Nor Aripin (New Century Health Publishers, Llc, 2024)
Non-Indexed Publication